Shura in the View of Muhammad Rasyid Ridho - Muhamad Fajar Pramono; Taufiqurrohman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
In the discourse of Islamic political thought, spanning both pre-modern and contemporary eras, the concept of